Catalyst–Electrolyte Interactions in Aqueous Reline Solutions for Highly Selective Electrochemical CO2 Reduction. Issue 2 (20th January 2020) - Garg, Sahil; Li, Mengran; Rufford, Thomas E.; Ge, Lei; Rudolph, Victor; Knibbe, Ruth; Konarova, Muxina; Wang, Geoff G. X.
Abstract: Invited for this month′s cover is the group of Tom Rufford at the University of Queensland. The image shows how choline chloride and urea in a reline solution interact with the surface of a silver cathode to enhance the selectivity of electrochemical CO2 reduction to CO. The Full Paper itself is available at 10.1002/cssc.201902433 . Abstract : "… restructuring the surface of a silver catalyst" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201902433 . View the Front Cover here: 10.1002/cssc.201903391 .